IMPLEMENTATION DETERMINATION OF EMPLOYEES TO INCREASE THE BEST POSITION IN. YES COMMUNICATION USING WEB-BASED PRODUCT WEIGHTED - Muhardi Saputra; Roberto Viali Hutabarat; Galih Agung Prayogo; Mawarni Munte; Yunika Putri Limbong (Universitas Negeri Medan, 2019)
Abstract: Employees are one of the most important asset for a company. Therefore, the company should be able to continue to control and motivate the employees to remain willing to work in his company. One way that can be done by the company to support the performance of employees is to select the best employees each year. There are many methods that can be used to determine the best employees. One of these methods Weighted Product. Weighted Product is a method that uses an alternative multiplication on the existing rating criteria and memangkatkannya in accordance with the weighting of the criteria that have been provided by the company. In this way this calculation the company can determine the best employees accurately and quickly. Keywords : Best Employee, Position, Weighted Product (WP), Web. Abstrak: Karyawan merupakan salah satu aset terpenting bagi sebuah perusahaan. Oleh karena itu, pihak perusahaan harus dapat terus mengontrol dan memotivasi pihak karyawannya agar tetap bersedia bekerja sama di perusahaannya. Salah satu cara yang dapat dilakukan oleh pihak perusahaan untuk mendukung kinerja karyawannya adalah dengan memilih karyawan terbaik setiap tahunnya. Ada banyak metode yang dapat digunakan untuk penentuan karyawan terbaik. Salah satunya metode Weighted Product. Weighted Product merupakan metode yang menggunakan perkalian pada alternatif rating yang ada di kriteria lalu memangkatkannya sesuai dengan bobot dari kriteria yang telah disediakan oleh perusahaan. Dengan cara ini perhitungan ini pihak perusahaan dapat menentukan karyawan terbaik dengan tepat dan cepat.